(untitled) (Al-Mansour Journal, 2022)
The research aims at clarifying the relationship between the identification of the training needs and the knowledge gap of the organization in the Iraqi Ministry of Transport, based on the problem of research "is how the process of identifying the training needs contribute to reducing the knowledge gap of the organization in the Iraqi Ministry of Transport", and highlights the importance of research focus on the need to focus on identifying needs Training in a manner that helps to reduce and fill the knowledge gap of the organization in order to keep up with developments in the field of administrative work in the ministry above. The first is the independent variable: identification of the training needs in their dimensions (organization analysis, performance gap, design of the training program), and the second variable dependent: the knowledge gap of the organization in its dimensions (assessment of the current state of knowledge, identification of cognitive requirements, The sample was (82) members of the general managers assistants and directors of departments and divisions at the ministry’s headquarters. The questionnaire was adopted as a main tool for data collection. The spss program was used to measure, analyze and test the hypotheses and interpret the results for research. The study hypothesized that there is a correlation relationship and a relationship of significant statistical significance between the identification of the training needs and the knowledge gap of the organization. The research Was reached on a set of conclusions and recommendations Benefit from him the researchers and the organization in searched place